FOREIGN COMPANIES’ ACTIVITIES IN THE TURKESTAN GENERAL GOVERNORSHIP - Xusanov Jahongir Abdimo’minovich; Xasanova Zarrina Shadiyarovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article is devoted to the activities of foreign companies in the Turkestan General Governorship. The role of foreign investors (Gerhard and Gay, the Kraft brothers, the Knop brothers, Louis Zalma, the Schlossberg brothers, and the “Beshbosh” joint-stock company) in the country’s infrastructure, local winemaking, and silk production is analyzed.